SUSTAINABILITY NAVAL BASE WITH THREE MAIN ASPECTS AS ONE OF THE INDONESIAN MARITIME DEFENSE AND SECURITY ELEMENTS WITH SYSTEM DYNAMIC APPROACH - Indra Agustian; Avando Bastari; Okol Sri Suharyo (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2019)
The development of Naval Base requires very strategic planning and calculation to obtain the sustainability of the base. This is intended so that in the future the existence of these bases can continue and exist, which is not disturbed by changes and System Dynamics from various aspects that develop and change over time. Sustainability of Naval Base is determined by many factors that are interrelated with one another as a very complex system arrangement so that a comprehensive analysis of various related aspects of the researcher is compiled into Three main aspects namely Defense Security Political Aspects, Economic Aspects and physical aspects of naval base. In this paper, the researcher will compile a model with System Dynamics approach to the sustainability of the Naval Base that is the object. Then also use Fuzzy Weighting from the elements of subjectivity which will be projected to become elements of objectivity, which also involves data / variables that are qualitative and quantitative. This has never been discussed in previous site selection studies. The complexity of the variables and the dependency relationships between variables in the system, and the decision makers' subjectivity can be identified and smoothed with the Fuzzy Weighting to get the weighting value so that the integration between the System Dynamics model with the Fuzzy Weighting method gets the analysis results of the Naval Base sustainability system based on three main aspects namely Defense Security Political Aspects, Economic Aspects and Physical Aspects of Naval Base. The results of the assessment of Fuzzy Weighting put the Defense Security Political Aspects in the first place with the value of the weight of the influence of interest 3.60, followed by the second position of the Physical Aspects of Naval Base with the value of the weight of the influence of the interest 3.40 and in the third position the Economic Aspects with a value of 3.0. Then the results are integrated into the System Dynamic calculation that produces sustainability values from three main aspects including Defense Security Political Aspects with strategic value of base area 36.42, then from Economic Aspects with land availability value 3.94, and Physical Aspects of Naval Base with physical capability values base 21.07. Keywords: Naval Base, Sustainability, Three Main Aspects, Fuzzy Weighting, System Dynamic.